Surface modification of ZnO quantum dots by organosilanes and oleic acid with enhanced luminescence for potential biological application - Rissi, Nathalia Cristina [UNESP]; Hammer, Peter [UNESP]; Chiavacci, Leila Aparecida [UNESP] (IOP Publishing, 2017)
Luminescent ZnO-QDs is a promising candidate for biological application, especially due to their low toxicity. Nevertheless, colloidal ZnO-QDs prepared by sol-gel route are unstable in water and incompatible with lipophilic systems, hindering their application in biology and medicine. To tackle the problem, this study reports three different strategies for surface modification of ZnO-QDs by: (i) hydrophilic (3-glycidyloxypropyl) trimethoxysilane (GPTMS), (ii) hydrophobic hexadecyltrimethoxysilane (HTMS) and then by (iii) oleic acid (OA) and HTMS bilayer. Capped ZnO-QDs by GPTMS and HTMS were performed by hydrolysis and condensation reactions under basic catalysis, leading to the formation of siloxane layer, involving strong interaction between the silanes with hydroxylated surface of ZnO, thereby creating a covalent bond-ZnO-O-Si. Alternatively, OA and HTMS were employed as hydrophobic agent to form a bilayer barrier surrounding the nanoparticles (NPs). Capped ZnO-QDS were analyzed by techniques including: Fourier transform infrared spectroscopy, x-ray photoelectron spectroscopy, x-ray diffraction and transmission electron microscopy, as well as the monitoring of excitonic peak of ZnO by UV-vis absorption spectroscopy. Photoluminescence measurements confirmed the importance of capping agents. Bare ZnO-QDs powder showed lowest photoluminescence intensity and displacement to yellow region when compared with ZnO-QDs capped, which present a higher photoluminescence in the green region. The above results can be related to changes of the concentration of oxygen vacancies (Vo) and also by increased presence of surface defect density. Silane capping represents the best choice for high stability and photoluminescence enhancement of ZnO-QDs.
Keywords: Photoluminescence; Quantum dots (QDs); ZnO